Sistem Identifikasi Penduduk Berbasis Gambar Finger Print - Suhendro Yusuf Irianto; Wahyu Nugroho (Jurnal Informatika, 2010)
In this paper we try to demonstrate the use Visual Basic 6.0 to develop a finger print based  social security (KTP) in kecamatan Tanjung Karang Barat. Tanjung Karang Barat Residents application demonstrates, the new system able to eradicate mistyping or human error, social security duplication, long time processing, unnecessary bureaucracy.    Above and beyond its advantages, the system be further developed to improve security, reliable backup, and  shoul be available on line in the near future. Keyword : Finger print, KTP, visual  basic 6.0, Tanjung Karang Barat